Keratosis Seboroik Bertangkai yang Diterapi dengan Elektrodesikasi dan Elektrokauter pada Pasien Diabetes Melitus - Hanifia Ulfa Fawzia; Dimas Djohan Sukandar Putra (Green Publisher Indonesia, 2026)
Seborrheic keratosis (SK) is a benign neoplasm most commonly found in the facial region in elderly. SK appears as a cutaneous manifestation in 15% of diabetes mellitus patients due to excessive proliferation of keratinocytes and melanocytes. Clinically, SK sometimes mimics basal cell carcinoma, cutaneous cornucleosis, and malignant melanoma, histopathological examination is necessary to distinguish each diagnosis.Publication about SK in DM is still limited nowadays. A 64-year-old woman with black spots on her face that have been getting bigger over the pastyear, increasingly painful and itchy. The patient has been working under sunlight for 50 years without sunscreen and has been undergoing diabetes treatment for the past 5 years with glimepiride 1x2mg. Electrodesiccation and electrocauterization were performed for further histopathological examination of the tissue. The clinical manifestation of SK is multiple or solitary, yellowish-brown, pedunculated lesions of varying sizes. Adefinitive diagnosis is made by histopathological examination showing hyperkeratosis and acanthosis. The risk factors for SK are not yet fully understood, but are thought to involve mutations in FGFR3, PI3K, and IGF. Therapy is based on available modalities and patient preference. There were no significant differences in efficacy, healing duration, symptoms, and recurrence among these therapy options. KS occurs due to various unclear risk factors, one of which is metabolic disorders such as diabetes mellitus. Clinically, atypical KS often resembles otherlesions, necessitating histopathological examination. Research on KS in DM patients is still limited, requiring further research